THE LINGUOPRAGMATIC FOUNDATIONS OF THE "STEPPARENT" CONCEPT IN FOLKLORE FAIRY TALES - Kаyumоvа Mоhinur Murоdullаyevnа (Bright Mind Publishing, 2025)
This article examines the linguopragmatic foundations of the "step-parent" concept in folklore fairy tales. The study focuses on how this concept is semantically, pragmatically, and culturally represented in oral tradition. Using examples from Uzbek folk tales, we explore the pragmatic functions of speech acts, implicatures, and presuppositions related to step-parents and step-children. The research highlights that while the "step-parent" concept is often portrayed negatively, there are cases where it takes on a more neutral or even positive connotation. The findings reveal that linguistic and cultural factors shape the perception of step-parental relationships in fairy tales, reinforcing social values and moral lessons.
Keywords: Linguopragmatic, step, step-parents, concept, fairy tales, aspect, cultural.